Substantiation of Cumulative Coefficient Characterizing Epidemic Typhus Fever Transmission Activity Depending on Seasons - E. P. Lukin; S. L. Kirillova; V. B. Kirillov (Проблемы особо опасных инфекций, 2009)
Monthly distribution of epidemic typhus fever morbidity during epidemics arisen since the end of XIX up to the middle of XX century has been analyzed. The cumulative coefficient considering a set of factors which effect the epidemic typhus fever morbidity is substantiated. This coefficient can be used to forecast the scale of this infection outbreaks in case of its introduction from endemic regions or recurrence of Brill's disease.